A framework for evaluating the effectiveness of conservation attention at the species level - Milner-Gulland,EJ; Baillie,J; Washington,H; Waterman,C (Oryx, 2014)
It is essential to understand whether conservation interventions are having the desired effect, particularly in light of increasing pressures on biodiversity and because of requirements by donors that project success be demonstrated. Whilst most evaluations look at effectiveness at a project or organizational level, local efforts need to be connected to an understanding of the effectiveness of conservation directed at a species as a whole, particularly as most metrics of conservation success are at the level of species. We present a framework for measuring the effectiveness of conservation attention at a species level over time, based on scoring eight factors essential for species conservation (engaging stakeholders, management programme, education and awareness, funding and resource mobilization, addressing threats, communication, capacity building and status knowledge), across input, output and outcome stages, in relation to the proportion of the species’ range where each factor attains its highest score. The framework was tested using expert elicitation for 35 mammal and amphibian species on the Zoological Society of London's list of Evolutionarily Distinct and Globally Endangered species. Broad patterns in the index produced by the framework could suggest potential mechanisms underlying change in species status. Assigning an uncertainty score to information demonstrates not only where gaps in knowledge exist, but discrepancies in knowledge between experts. This framework could be a useful tool to link local and global scales of impact on species conservation, and could provide a simple and visually appealing way of tracking conservation over time.